IMPLEMENTASI PENINGKATAN LITERASI KEUANGAN UNTUK MENCIPTAKAN SDM UNGGUL PADA SISWA DAN SISWI SMK NEGERI 7 KOTA SERANG - Rohmansah, Nur; Setiawan, Arip Budi; Susiani, Ina; Saksana, Fenizar Rizky; Handayani, Heni (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
The Community Service Program (PKM) is motivated by the rapid development of the digital economy, which requires young generations to possess adequate financial literacy so they can plan, manage, and utilize their finances wisely. However, preliminary observations at SMK Negeri 7 Kota Serang indicate that most students have not yet mastered personal financial planning, basic transaction recording, or the use of technology-based financial services. This condition may hinder their readiness to meet the demands of the workforce and entrepreneurship. Therefore, this Community Service initiative aims to improve students’ financial literacy in order to develop superior, independent, and competitive human resources in the financial sector. The methods applied in this program include seminars, training sessions, and hands-on practice. The materials cover the fundamentals of personal financial management, budgeting, saving and investment strategies, as well as the introduction of digital financial technologies such as e-wallets and financial recording applications. The activities were conducted interactively through discussions, simulations, and case studies, involving students from the finance expertise program as the primary participants. Quantitative indicators of success were established, including: a minimum 30% increase in financial literacy scores based on pre-test and post-test results; 80% of participants being able to prepare a simple budget correctly; and 75% being able to independently use digital financial recording applications. The results of the program show a significant improvement in participants’ understanding and skills related to budgeting, transaction recording, and the wise use of digital financial services. Participants also demonstrated more positive attitudes toward saving habits and daily financial management. The outputs of this program include an activity report, video documentation, and publications on online media or community service journals. With improved financial literacy, students are expected to develop financially intelligent character that supports their success both in the workforce and in entrepreneurship. This program serves as a strategic step in preparing younger generations to compete in the era of the creative and digital economy.